Using the Abridged Version of Some Novels as a Way to Encourage Students' Written and Oral Production (GIST – Education and Learning Research Journal, 2018)
This article analyzes the effect of working with the abridged version of some novels in order to promote students’ communication in English. Two fourth semester English courses, from a private university, were randomly chosen to develop the different activities during one semester. The data was collected through students’ written papers, the researchers’ journal and a questionnaire. The findings show that students’ constant work with this kind of literature, as well as the teachers’ feedback, were factors that motivated their language use improvement; thus, they learned new expressions, did written and oral training, and acquired knowledge thanks to the contact with other cultures through literature.
Keywords: action research; abridged novels; listening exercise; written and oral practice